Shrink rap - Parker, Robert B. (New York : G.P. Putnam's Sons, 2002)
Boston private detective Sunny Randall agrees to protect a touring writer from her abusive ex-husband, but she quickly learns that the stalker in question is much more sophisticated, intelligent, and potentially deadly than most.
"A Sunny Randall novel"--Jacket.
88731
Keywords: Randall, Sunny (Fictitious character) -- Fiction; Women private investigators -- Massachusetts -- Boston -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction